Bentuk Penyajian Tari Manggang Kemplang Oleh Sanggar Kipas Emas Di Kelurahan Timbangan Ogan Ilir - Erinna Rahmalia; A. Heryanto; Nofroza Yelli (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
Manggang Kemplang Dance is a dance that tells about the manggang kemplang tradition which reflects the local wisdom of the Ogan Ilir people in utilizing natural resources and local wisdom in processing food which is danced by 5 dancers. The problem in the research is the form of presentation of the Manggang Kemplang dance in Timbangan Village, Ogan Ilir Regency. The aim of this research is to find out and describe the form of presentation of the Manggang Kemplang dance by the Golden Fan Studio in Timbangan Village, Ogan Ilir Regency. This research uses qualitative methods with data collection techniques in the form of observation, interviews, documentation and literature study. The form of presentation of the Manggang Kemplang dance consists of aspects of choreographic elements which include dance movements, dance space, accompaniment/accompaniment music, dance title, dance theme, dance type, mode of presentation, dancers, fashion, make-up, lighting and props. .